Music Education Reform for Muscular Disease Prevention and Treatment - Quan, Huiqi (Journal of Roi Kaensarn Academi, 2023)
The incidence of neuromuscular and skeletal diseases related to performance am keyboard instrument players has been high, often limiting or terminating their learning and playing careers. Injured pianists are eager to find solutions and so-called scientific methods to develop injury prevention techniques, but these methods have not been seriously studied. Based on the researcher's 5 years of full-time and part-time teaching reform practice in the Keyboard and Instrument Department of Inner Mongolia Academy of Arts, this study investigated an interdisciplinary and nontraditional piano teaching method - the Piano Performance Method of Juilliard Conservatory of Music. This method has received considerable public praise from industry insiders, but no systematic research has been conducted to determine its efficacy in restoring and preventing neuromuscular bone diseases and recurrence, as well as its impact on technology The influence of musicality and extra muscular factors. Participants include undergraduate and graduate students, amateur pianists (enthusiasts), and organists (enthusiasts) who have studied the method for at least two semesters between 2020 and 2022. An anonymous survey was conducted am 103 learners aged 22 to 72, of whom 74 (N=74) responded (71.8%), and 26 were interviewed in depth. The results of surveys and interviews indicate that participants believe that this method is very helpful in promoting the recovery of neuromuscular and skeletal diseases. The significance of the relationship between coding includes: the correlation between "effective" and "non injurious performance" of coding is 0.70, while the correlation between "effective" and "re performance" is 0.66. A single sample t-test of survey data also showed that this method has a positive perspective in helping to recover and prevent recurrence (p<.001). In addition, survey and interview participants have reported improvements in technology and musicality, and many have also reported improvements in their spare time lives. A single sample t-test of survey data shows that these improvements are significant at a level of 5% or higher. This study hopes that these data can serve as a starting point for the wider promotion of the Piano Performance Method of the Juilliard Conservatory of Music as a useful model for the teaching of injury prevention piano techniques for piano majors.